The Effect of Transformational Leadership on Work Performance through Job Satisfaction and Work Engagement as Intervening Variables: Case Study on Kantor Pengawasan dan Pelayanan Bea Cukai Tipe Madya Pabean Tanjung Emas Employees - Nabila Nurlitasari; Andriyani Andriyani; I Gede Ary Raditya Palguna; Edy Rahardja (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze how much influence the transformational leadership variable has on work performance through job satisfaction and work engagement owned by the employees of the Kantor Pengawasan dan Pelayanan Bea Cukai (KPPBC) Tipe Madya Pabean (TMP) Tanjung Emas. The data used in this study are primary data derived from the distribution of research questionnaires. The population in this study were permanent employees at KPPBC TMP Tanjung Emas as many as 242 people. The sample in this study were permanent employees at KPPBC TMP Tanjung Emas who had worked for at least 2 years, obtained as many as 120 respondents. The sampling technique used in this study is non-probability sampling. The sampling method in this research is purposive sampling. This research uses Structural Equation Modeling (SEM) analysis technique with AMOS 24.0 analysis tool. The findings show that transformational leadership has a positive effect on work performance, transformational leadership has an indirect effect on work performance through job satisfaction as a mediation (partial mediation) and transformational leadership has an indirect effect on work performance through work engagement as a mediation (partial mediation). This research shows that the leader must be able to be a good reflection for employees so as to increase job satisfaction. If employees are satisfied with their work, there will be an increase in work performance. In addition, work engagement will improve work performance because employees can work better in completing their tasks.